Investigating the Impact of External Debt on Economic Growth: A Case Study of Pakistan - IRUM SAJJAD; IRUM SAJJAD; DR. MUHAMMAD AZAM KHAN (Journal of Business & Tourism, 2021)
This article is an attempt to evaluate the effect of external debt on economic growth for during the period of 1980–2016. The Augmented Dickey Fuller (ADF) test is used for determining stationarity, whereas the ADF test results exhibit that the variables used found are . The empirical results indicate that external debt and total debt service have deleterious and statistically significant impacts on GDP growth rate. The other explanatory variables namely human capital by life expectancy, exports, and Foreign Direct Investment (FDI)reveals significantly positive significant influence on GDP growth rate. Appropriate policy should be adopted by the policy makers to reduce external debt, increase volume of exports and enhance more foreign investment, it will boost economic growth in the country.